ChemInform Abstract: Iron Porphyrin‐Catalyzed Three‐Component Reaction of Ethyl Diazoacetate with Aliphatic Amines and β, γ‐Unsaturated α‐Keto Esters. Issue 21 (27th May 2014) - Ma, Chaoqun; Xing, Dong; Zhai, Changwei; Che, Jiuwei; Liu, Shunying; Wang, Jue; Hu, Wenhao
Abstract The structure of the product (IVd) is confirmed by X‐ray analysis.